PELATIHAN PEMBUATAN YOGHURT KEPADA KELOMPOK TANI PEREMPUAN DI DESA SEPAWON, KECAMATAN PLOSOKLATEN, KABUPATEN KEDIRI - Tanjungsari, Ardina (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
The Sepawon Village Women's Farmers Group is a milk producing farmer group in Sepawon Village who usually sells milk to the cooperative at a price of 8000/L. The aim of UNP Kediri Animal Husbandry Study Program Community Service Team in collaboration with the Sepawon Village Women's Farmers Group to increase the economic value of milk by making fermented dairy products. Yogurt is a dairy product that can add economic value by fermenting it using the bacteria Lactobacillus bulgaricus and Streptococcus thermophilus. The benefit of consuming yoghurt is that it balances good bacteria in digestion and reduces toxic substances in the body. The process of making yoghurt involves heating the milk to be fermented at a temperature of 90°C for 15-30 minutes, after that the milk is cooled until the temperature reaches 40°C, then packaged in plastic bottles. Community Service Activities are carried out by means of Pre-Training, Yoghurt-making Training (Presentation and Demonstration) and post-test to determine participants' understanding. The results of Community Service showed that the Sepawon Village Women's Farmers Group participants were enthusiastic about taking part in the yoghurt making training. The post test results also showed that the participants were committed to independently continuing the practice of making yoghurt at home to increase the economic value of milk and farmer welfare.